Identificação de perdas volumétricas em um sistema de abastecimento de água no município de Belo Horizonte / MG - Almeida, Ailton de; Fontes, Pedro Emílio Ribeiro (PARAMÉTRICA, 2010)
This study aims to assess, understand and quantify water loss index, in a treated water distribution system of a sanitation concessionaire, and to know the reduction ways of these losses by field research, in a small region that belongs to Olhos D’Água Neighborhood, west of Belo Horizonte. Supported in the waste rates and considering the preciousness of this natural resource, it is emphasized the necessity of an efficient management in the water loss fight control. The adopted methodology was data-collection and exploratory research, or survey on the field. The results in the waste fight reinforce the necessity of implementation of all presented knowledge and methods. As conclusion the work identifies the necessity of the water loss reduction, having as improvement due the reduction of these losses, financial gains with the turnover increase, costs reduction by providing less treated water availability; and with the environmental point of view, the water preservation, getting throughout the years the availability of the cited natural resource for the future generations. Because once reduced its withdrawal, the useful life increases in the exploited area, whether lake, river or artesian wells or another water course.